ANALYSIS OF PRODUCT QUALITY AGAINST DECISION OF PURCHASING KERUPUK HALAL IN CIAMIS DISTRICT - Fitrnaty Adirestuty; Ika Dartika; Tsania Salsabila (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2021)
Halal